Clinical pharmacists as medication therapy experts in diabetic clinics in Saudi Arabia - Not just a perception but a need - Hafiz A. Makeen (Elsevier, 2017)
The pharmacist's role is expanding from medication dispensing to patient care. There are several newer horizons in which clinical pharmacists have a vital role to play such as diabetic care, handling asthma patients, pain management, anti-coagulation therapy and in hyperlipidemia. Among these, the disorder that is perceived to reach epidemic proportions globally is diabetes mellitus. In the Arab world, particularly in countries like Saudi Arabia, the number affected and the cost incurred in the management of diabetes are relatively high. Apart from adding to the economic burden, the complications arising due to a lag in identification and management are manifold. In developed countries, several practicing hospitals and clinics have inducted clinical pharmacists as vital members of the healthcare team. With profound knowledge about medications, clinical pharmacists are inclined to stay abreast with recent developments in research and latest guidelines, thus supporting physicians in evidence based practice. Clinical pharmacists through Medication Therapy Management can render services by guiding, identifying and monitoring drug related issues faced by the patients. This can contribute in reducing the prevalence of diabetes mellitus and improving the quality of life. To keep pace with the growing prevalence of diabetes in the kingdom, clinical pharmacists need to undergo specialized training in high risk areas. Health regulating bodies should be keen in adopting provisions of inducting them in discrete specialties which can also help in trimming heathcare expenditure.